(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
Both the theoretical and practical elements of translation studies are addressed by the science of translation. The goal of translation theory is to theoretically describe the phenomenon of translation. In the linguistic theory of translation, contact between communicants who speak different languages is established through translation as a sort of voice communication. The implications of this theory basis is macrolinguistics, which includes all of its new branches, including psycholinguistics, sociolinguistics, text linguistics, communicative linguistics, etc.